2009
DOI: 10.1111/j.1741-2358.2008.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with remaining teeth of older adults in the state of São Paulo, Brazil, 2002

Abstract: Objectives: The objective of this study was to verify the association between the number of teeth present with socio-demographic and economic variables and with the access to dental services and self-perception of oral health among the elderly. Materials and Methods: The sample was composed of individuals from 65 to 74 years of age, which was representative of the state of São Paulo (n = 781). In this study, the analysis of data considered dentate elderly only, who were divided into two groups: those with one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 33 publications
3
15
1
4
Order By: Relevance
“…Other studies have also identified age as a risk factor for tooth loss. 4,5,18,20,21 The influence of age on tooth loss may have a cohort effect, which is explained by differences in national health policies implemented in the country's history. In Brazil and worldwide, the practice of tooth extraction accompanied the increasing incidence of caries in the 16 th and 17 th centuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also identified age as a risk factor for tooth loss. 4,5,18,20,21 The influence of age on tooth loss may have a cohort effect, which is explained by differences in national health policies implemented in the country's history. In Brazil and worldwide, the practice of tooth extraction accompanied the increasing incidence of caries in the 16 th and 17 th centuries.…”
Section: Discussionmentioning
confidence: 99%
“…As in this study, other studies have also observed an association between lower income and tooth loss. 4,5,20 The main reason for participant's choice of tooth extraction rather than treatment seemed to be financial. 23 The reasons for tooth loss are complex, involving not only physiological causes and socioeconomic associations, but also other factors such as personal attitudes and beliefs.…”
Section: 17mentioning
confidence: 99%
See 1 more Smart Citation
“…24 These health problems have a negative impact on the daily life of the individual, as they create functional difficulties, problems chewing and talking, and problems with sociability, such as being unhappy with appearance, difficulties being accepted socially and limiting access to the job market. 25 Oral health problems are measured using clinical indices.…”
mentioning
confidence: 99%
“…Estudos brasileiros demonstraram que a situação epidemiológica da população em relação ao edentulismo e a perda precoce do dentes é um grave problema [4,13,14]. Observar que 14,5% e 36,4%, do grupo etário entre 15 a 19 anos, precisam de algum tipo de reabilitação no arco superior e inferior, respectivamente, é um dado alarmante.…”
Section: Metodologiaunclassified